Mitigating the Overheat of Stretchable Electronic Devices Via High-Enthalpy Thermal Dissipation of Hydrogel Encapsulation - Cao, Can (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.